SINKRONISASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 12 TAHUN 1998 TENTANG RENCANA UMUM TATA RUANG TERHADAP UNDANGUNDANG NOMOR 1 TAHUN 2011 TENTANG PERUMAHAN DAN KAWASAN PERMUKIMAN DALAM PEMANFAATAN RUANG UNTUK KAWASAN PERMUKIMAN DI KOTA PEKANBARU - Sinaga, Yusril Fahmi; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Basically, meeting the need for a house as a place to live or occupy is theresponsibility of the community itself. However, the government, local governments, andprivate companies engaged in housing development are encouraged to be able to assist thecommunity in meeting the need for a house as a place to live or shelter. In the use of space forresidential areas in Pekanbaru City is not evenly distributed, we can see this from the divisionof clustered built areas. Therefore, the Government must make a policy to even out thedevelopment of residential areas. The purpose of writing this thesis, namely: First, todetermine the synchronization of Pekanbaru City Regional Regulation No. 12 of 1998concerning the General Spatial Plan of Law no. 1 of 2001 concerning Housing and SettlementAreas in spatial use for residential areas in Pekanbaru City. Second, to determine the role ofthe Government in the use of space for housing and residential areas.This research is a sociological juridical legal research, which is a research approachthat emphasizes the legal aspects (laws and regulations) with respect to the subject matter tobe discussed, linked to the realities in the field. This study uses primary data sourcesconsisting of primary, secondary and tertiary legal materials.From the research results, it is concluded that, first, that the synchronization betweenPekanbaru City Regional Regulation Number 12 of 1998 concerning General Spatial Planningwith Law Number 1 of 2011 concerning Housing and Settlement Areas fully supportspreserving the environment by utilizing space for residential areas according to with itsdesignation as long as it does not conflict with statutory regulations. By directing policieswisely in controlling spatial use through zoning regulations, licensing, providing incentivesand disincentives, and imposition of sanctions. Second, the role of the Pekanbaru CityGovernment is an embodiment of the distribution of powers in carrying out governmentaffairs, having full authority to regulate its own regional household affairs as mandated inArticle 18 of the 1945 Constitution of the Republic of Indonesia. As well as Pekanbaru CityGovernment can maximize the existing space by minimizing the obstacles that occur.Keywords: Synchronization-Spatial Use– Settlement Areas